Experimental Study on Creep Characteristics of Unloaded Rock Masses for Excavation of Rock Slopes in Cold Areas - Xingzhou Chen; Hai Jiang; Lili Chen; Wei Du; Sheng Gong (Applied Sciences, 2023)
Seasonal freeze–thaw environments are one of the key factors that aggravate the mechanical strength decay of excavated and unloaded rock masses on reservoir banks in cold areas. To study the time-dependent mechanical properties of an excavated and unloaded rock mass on a bank slope under freeze–thaw action, triaxial unloading tests were carried out on sandstone, freeze–thaw tests simulating freezing strength were conducted, and triaxial creep tests were implemented with graded incremental loading on unloaded specimens subjected to freeze–thaw action. The test results showed that the total deformation of the unloaded specimens is significantly increased compared with the conventional specimens, and the lateral direction is more likely to produce creep behaviour than the axial direction. The level of confining pressure determines the level of creep deformation of unloaded specimens and affects the variation law of creep rate. The creep behaviour of the unloaded specimens is aggravated by freeze–thaw action and, the longer the freezing period, the larger the creep strain share, and the creep rate increases significantly. The creep damage pattern of the unloaded specimens subjected to freeze–thaw action is mainly manifested as shear damage, and the creep process intensifies the derivation of tension-type cracks in the specimens. The higher the confining pressure of the unloaded specimen, the more obvious the plastic characteristics and the weaker the brittle characteristics during creep failure. The freeze–thaw action significantly reduces the long-term strength of the unloaded specimen, which is approximately 50~55% of the instantaneous strength. The long-term strength decays significantly with an increasing freezing period, and the research results can provide a theoretical reference for the evaluation of the long-term stability of excavated and unloaded rock masses in cold areas.